2014
DOI: 10.1080/01932691.2013.807741
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of SPR Nanosensor Using Gold Nanoparticles and Self-Assembled Monolayer Technique for Detection of Cu2+in an Aqueous Solution

Abstract: In this work, we investigated the fabrication of surface plasmon resonance (SPR) nanosensor using gold nanoparticles (AuNPs) chemisorbed onto self assembled monolayer of 10-(3-amino phenoxy) decane-1-thiol on gold substrate. The fabrication process of SPR nanosensor was characterized using different techniques such as infrared reflection-absorption spectra (IRRAS), xX-ray photoelectron spectroscopy (XPS), and atomic force microscope (AFM). The fabricated SPR nanosensor was used for detection of Cu 2þ in an aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Past studies have shown that current SPR methods can detect approximately 100 ng/L proteins [ 16 ], which sensitivity is sometimes insufficient for measuring samples. During recent years, colloidal gold nanoparticles have been widely used as a label for analytical signal amplification [ 17 , 18 ]. They possess advantages such as narrow size distribution, rapid and easy synthesis, efficient surface modification, and desirable biocompatibility [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have shown that current SPR methods can detect approximately 100 ng/L proteins [ 16 ], which sensitivity is sometimes insufficient for measuring samples. During recent years, colloidal gold nanoparticles have been widely used as a label for analytical signal amplification [ 17 , 18 ]. They possess advantages such as narrow size distribution, rapid and easy synthesis, efficient surface modification, and desirable biocompatibility [ 19 ].…”
Section: Introductionmentioning
confidence: 99%